Os benefícios e desafios do bilinguismo na infância e o desenvolvimento cognitivo e cerebral - Dassi, Camila Caroline Oliveira (2018)
Acquiring or developing a second language during in childhood can bring innumerable benefits to the human being, since the main tool of communication in the world is language and it is through language that we interact socially adding various social relations experiences throughout life. Thus, this undergraduate thesis aims to make a bibliographical review on bilingualism and especially the benefits found in acquiring a second language in childhood, later to present the challenges that can be found during this course and to comment on some cognitive and cerebral aspects that involve this process. To reach this goal the research will be based on literature data that refer to the theme. The data will be analyzed in order to understand the contribution of studies on bilingualism in childhood to our society and for future research, reflecting on the advantages and challenges encountered in the acquisition process of a second language, taking into account the individual and social characteristics of each apprentice.